Clinically-Weighted Probabilistic Tractography Mapping of Pallidal Deep Brain Stimulation for Parkinson's Disease. (16th November 2020) - Kashanian, Alon; Malekmohammadi, Mahsa; Flagg, Mitchell; Riskin-Jones, Hannah; Sparks, Hiro; Pouratian, Nader
Abstract: INTRODUCTION: Deep brain stimulation (DBS) of the globus pallidus internus (GPi) is a widely accepted treatment for Parkinson's disease (PD), yet there is intersubject-variability in outcome that is not yet fully understood. We hypothesize that connectivity data can be used as an independent biomarker of GPi DBS efficacy in individuals with PD. METHODS: We evaluated imaging in 35 patients that underwent bilateral DBS of the GPi for PD. LEAD-DBS was used to model the volume of brain tissue activated (VTA) and FSL was used to perform probabilistic tractography from the VTA to the whole brain. We combined all individual tractography results in standard space to create a common population map. Not all patients had clinical scores available. For the 10 that did, we binarized their individual tractography maps and weighted them based on the percent clinical improvement in UPDRS part III scores from pre-operative OFF medication to postoperative OFF medication, ON stimulation. The resulting clinically-weighted maps were transformed into standard space and averaged. RESULTS: The common population map demonstrated strongest connectivity to the prefrontal cortex, brainstem, and thalamus. Superior clinical improvement was associated with voxels with greatest connectivity from the VTA to these brain regions. CONCLUSION: Probabilistic tractography revealed the prefrontal cortex, brainstem, and thalamus as imaging biomarkers associated with superior clinical outcome in pallidal DBS for PD. Clinically-weighted tractography maps may potentially be used with a reverse algorithm to identify the optimal region of the GPI for stimulation.